Kelayakan Ekstrak Biji Kopi Robusta (Coffea Canephora) sebagai Sediaan Krim Lulur - Aziza, Nurul; Dewi, Siska Miga (MASALIQ, 2023)
Obstruction of dead skin cells on the skin can cause premature aging, so it requires cosmetics that can remove dead skin cells. Treatments that are carried out directly on the skin to make it look beautiful and healthy are using scrub cosmetics. Coffee contains chemical compounds such as caffeine, polyphenols and chlorogenic acid. Chlorogenic acid in Robusta coffee is a natural antioxidants which is useful for moisturizing and smoothing the skin. Purpose: to analyze the preparation of scrub cream using robusta coffee bean extract in terms of laboratory tests, organoleptic tests, and hedonic tests. Method: this research method is an experimental research method with a quantitative approach. The results of research conducted based on the results of the organoleptic test and hedonic test showed that the texture, color, scent, and preference of the panelists had quite good assessment results. Laboratory tests on F0, F1, and F2 of the robusta coffee bean extract scrub cream showed that the pH test results were in accordance with the skin pH standards, namely 4-7, and the homogeneity test showed that the preparations F0, F1, and F2 were homogeneous. In conclusion: Robusta coffee bean extract scrub cream is feasible to be used as scrub cream seen from laboratory tests (pH test and homogeneity test), organoleptic test (texture, color, and scent), and hedonic test (panelist preference).